THE ROLE OF STORY-BASED LEARNING IN DEVELOPING GRAMMAR SKILLS AMONG PRIMARY SCHOOL LEARNERS (Лучшие интеллектуальные исследования, 2025)
The acquisition of grammar in primary education is a critical step toward linguistic competence, yet traditional methods often fail to engage young learners effectively. This paper investigates the pedagogical benefits of story-based learning (SBL) in the context of grammar instruction for primary school students. It emphasizes how integrating grammar into meaningful narrative contexts enhances comprehension, retention, and learner motivation. Drawing on theoretical frameworks and practical classroom observations, this study offers evidence supporting the use of SBL as a dynamic, child-centered strategy in language instruction.Освоение грамматики в начальном образовании — это важный этап на пути к языковой компетенции, однако традиционные методы зачастую не обеспечивают достаточной вовлечённости младших школьников. В данной статье рассматриваются педагогические преимущества метода обучения на основе рассказов (story-based learning — SBL) в контексте преподавания грамматики учащимся начальной школы. Особое внимание уделяется тому, как интеграция грамматических структур в содержательные и значимые повествовательные контексты способствует лучшему пониманию, запоминанию и повышению мотивации учащихся. На основе теоретических основ и практических наблюдений в классе предоставляются доказательства эффективности данного подхода как динамичного и ориентированного на ребёнка метода обучения языку.